2015
DOI: 10.1016/j.cpr.2014.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status and antisocial behaviour among children and adolescents: A systematic review and meta-analysis

Abstract: Previous research on the association between socioeconomic status (SES) and child and adolescent antisocial behaviour has produced mixed findings showing variation in the strength of association. This systematic review and meta-analysis aimed to summarise evidence on the relationship between socioeconomic status and broadly conceptualised antisocial behaviour, investigating variation across a range of antisocial subtypes and other potential moderators, including age, sex and informant. We identified 133 studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
142
2
6

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(168 citation statements)
references
References 54 publications
18
142
2
6
Order By: Relevance
“…Research has shown that sociopathy at least includes two aspects: (1) Primary sociopathy (interpersonal and emotional aspect) that includes apathy, narcissism, and acting against morality; and (2) secondary sociopathy which is the aspect of antisocial life style that includes behaviors that are considered impulsive, hostile, and irrational (3). Moreover, it has been shown that several risk factors are associated with antisocial behavior such as socioeconomic level (4) and violence (5).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that sociopathy at least includes two aspects: (1) Primary sociopathy (interpersonal and emotional aspect) that includes apathy, narcissism, and acting against morality; and (2) secondary sociopathy which is the aspect of antisocial life style that includes behaviors that are considered impulsive, hostile, and irrational (3). Moreover, it has been shown that several risk factors are associated with antisocial behavior such as socioeconomic level (4) and violence (5).…”
Section: Introductionmentioning
confidence: 99%
“…Children whose parents had low education levels were more likely to show peer relationship problems than children of parents with higher educational levels. Previous research on children's wellbeing and their parents' socioeconomic status (SES) suggests a similarly negative association, implying that mental health problems are more prevalent in children from families with a low SES than in children from higher socioeconomic backgrounds (Piotrowska, Stride, Croft, & Rowe, 2015;Rajmil, Herdman, Ravens-Sieberer, Erhart, & Alonso, 2014;Reiss, 2013). Several studies among children and adolescents from general population samples report similar negative associations between parental education and peer relationship problems (Havas, Bosma, Spreeuwenberg, & Feron, 2009;de Laat, Essink-Bot, van Wassenaer-Leemhuis, & Vrijkotte, 2016;Rajmil et al, 2014).…”
Section: Discussionmentioning
confidence: 58%
“…Parental psychopathological symptoms may influence children mental health (a) through predisposition to vulnerability genes (Cicchetti, 2016) because parents share approximately 50% of their genes with their biological offspring (Kim et al, 2009), and/or (b) through exposure offspring to higher adverse and non supportive environment, including poor parenting (Cimino et al, 2016), interparental conflict and (Breslend et al, 2016) a lower socio-economic status (Piotrowska et al, 2015).…”
Section: Problem Statementmentioning
confidence: 99%